2016
DOI: 10.3102/0002831216675719
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Interventions and School Discipline Sanctions in a Large Urban School District

Abstract: A large urban district ( N = 90,546 students, n = 180 schools) implemented restorative interventions as a response to school discipline incidents. Findings from multilevel modeling of student discipline records ( n = 9,921) revealed that youth from groups that tend to be overrepresented in suspensions and expulsions (e.g., Black, Latino, and Native American youth; boys; and students in special education) had similar, if not greater, rates of participation in restorative interventions than their peers. First-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 46 publications
2
80
0
2
Order By: Relevance
“…One study in Denver found that with each responsive intervention (circles, mediations, or conferences) a student received in the first semester of a school year after an office referral or suspension, the student's odds of receiving another office referral or out-of-school suspension in the spring semester were lower. This association held after accounting for demographics (including race), general or special education, frequency and seriousness of office referrals, and school environment (Anyon et al, 2016).…”
Section: Student Disciplinementioning
confidence: 90%
See 2 more Smart Citations
“…One study in Denver found that with each responsive intervention (circles, mediations, or conferences) a student received in the first semester of a school year after an office referral or suspension, the student's odds of receiving another office referral or out-of-school suspension in the spring semester were lower. This association held after accounting for demographics (including race), general or special education, frequency and seriousness of office referrals, and school environment (Anyon et al, 2016).…”
Section: Student Disciplinementioning
confidence: 90%
“…A different study in Denver found that the district's overall suspension rate fell from 11 percent to 6 percent between 2006 and 2013 while implementing restorative practices (Gonzalez, 2015). However, other studies (e.g., Anyon et al, 2014;Anyon et al, 2016;Gregory , et al, 2018) concluded from the Denver Public School data that restorative interventions were not associated with African American students having lower odds of receiving a suspension after a referral.…”
Section: Student Disciplinementioning
confidence: 92%
See 1 more Smart Citation
“…In the transformative view, equity means challenging oppression, including racism and classism (Dixson and Rousseau 2005). This perspective suggests that oppression is perpetuated through structural practices, such as racial disproportionality in discipline (Anyon et al 2016) or course placement , as well as educators' implicit biases and expectations (Warikoo et al 2016). This view also assumes intersectionality: individuals possess multiple social identities, and an understanding of oppression must consider the interactions among the dynamics of race, national origin, class, gender, language, ability, and other constructions (Crenshaw 1991;Solórzano and Bernal 2001).…”
Section: February 2019 177mentioning
confidence: 99%
“…Throughout this paper, we refer to RJ as a general framework for responding to school-based conflict; we use "RJ practices" or "restorative practices" to refer to specific practices or processes used to achieve the goals of RJ, like circles or mediations; and, "RJ response" describes an action or series of actions taken to address a given conflict or issue within an RJ framework, which may include multiple restorative practices or related supports. 2 While limited in number, a few comprehensive evaluations-including a recent randomized control trial in Pittsburgh-have found that schools engaged in RJ experienced decreases in behavioral incidents and use of suspensions; these studies have also found some reductions in racial disparities in school disciplinary responses, though the evidence is mixed (Anyon et al, 2016;Augustine et al, 2018;Davison, Penner & Penner, 2019;González, 2015b;Jain, Bassey, Brown, & Preety, 2014;Simson, 2012). Additionally, qualitative research has found that RJ contributes to meaningful changes in both school culture and disciplinary responses; fosters communication and accountability; and promotes empathy, social-emotional learning, and conflict resolution (González, 2015b;González, Sattler, & Buth, 2019;Jain et al, 2014;Vaandering, 2014;Wadhwa, 2016).…”
Section: Restorative Justice Practice and Research In Schoolsmentioning
confidence: 99%